Penerapan SAK EMKM berbasis Penggunaan QRIS dan Literasi Keuangan (Studi persepsi Pelaku UMKM Kuliner Tasikmalaya) - Yesti Siti Nurjanah; Taufik Wibisono (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
The writing of financial reports by culinary MSME players in Tasikmalaya is still experiencing obstacles due to the low understanding of financial literacy and the application of manual reporting systems. Although in fact, the preparation of financial reports that meet the standards will make it easier to get access to funding. To help make the quality of standard financial reports, this study aims to determine the effectiveness of financial literacy and the decision to use QRIS on the implementation of financial reporting based on SAK EMKM. this study uses a quantitative method with an explantory survey of culinary MSME players in Tasikmalaya who have used QRIS. The sampling technique used rondom sampling and managed to collect data from 158 respondents. The results showed that financial literacy contributed to the decision to use QRIS and SAK EMKM reporting. The decision to use QRIS makes the highest contribution to MSME actors in reporting finances based on SAK EMKM. The results of the study provide valuable direction for culinary MSME players in Tasikmalya that to facilitate the preparation of financial reports based on SAK EMKM, they can implement transactions with QRIS and continue to improve financial literacy. The limitations of this study only use research objects focused on Culinary MSMEs in Tasikmlaya and only examine the use of QRIS for financial reports. Suggestions for future research can conduct research with a wider and more diverse object, and can develop with other variables that can improve the quality of financial reports for business sustainability.